Runtime Task Scheduling for FPGA-Based Embedded Systems Using Just-in-Time Bitstream Prefetching - Alexis Duhamel; Sebastien Pillement (IEEE Access)
Dynamically and partially reconfigurable Field Programmable Gate Arrays (FPGAs) offer high performances and flexibility. These platforms can hot-swap reconfigurable regions to change the hardware behavior at the cost of a reconfiguration process. The scheduling of applications and their reconfiguration processes are then essential to respect timing constraints. In this paper, we introduce PF-PEFT, a scheduling heuristic for dynamically reconfigurable FPGA architectures. Results show that our approach reduces schedules duration by up to 13% compared to a comparable state-of-the-art approach.